2022
DOI: 10.1097/cej.0000000000000773
|View full text |Cite
|
Sign up to set email alerts
|

Dose-risk relationships between cigarette smoking and cervical cancer: a systematic review and meta-analysis

Abstract: Objective Cervical cancer (CC) is the fourth most frequent cancer worldwide. Cigarette smoking has been shown to influence CC risk in conjunction with human papillomavirus (HPV) infection. The aim of this study is to provide the most accurate and updated estimate of this association and its dose-response relationship. Methods Using an innovative approach for the identification of original publications, we conducted a systematic review and meta-analysis of studies published up to January 2021. Random effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
2
5
1
Order By: Relevance
“…In particular, NK activities in smokers are significantly reduced in comparison to those of non-smokers, and smoking seems to promote the acquisition or persistence of HPV infection through a reduction in the number of CD4+ lymphocytes, Langerhans cells, and local immune responses in the cervix [ 32 , 33 , 34 ]. These data are confirmed by a recent review and meta-analysis that showed a positive association between smoking and cervical cancer, independently from HPV infection, indicating that this association is dose-related and declines after the interruption of smoking [ 35 ]. In WLWH, the destruction of CD4+ cells by HIV combined with the effect of smoke may increase the likelihood of persistent HPV and the development of HPV-related lesions.…”
Section: Discussionsupporting
confidence: 67%
“…In particular, NK activities in smokers are significantly reduced in comparison to those of non-smokers, and smoking seems to promote the acquisition or persistence of HPV infection through a reduction in the number of CD4+ lymphocytes, Langerhans cells, and local immune responses in the cervix [ 32 , 33 , 34 ]. These data are confirmed by a recent review and meta-analysis that showed a positive association between smoking and cervical cancer, independently from HPV infection, indicating that this association is dose-related and declines after the interruption of smoking [ 35 ]. In WLWH, the destruction of CD4+ cells by HIV combined with the effect of smoke may increase the likelihood of persistent HPV and the development of HPV-related lesions.…”
Section: Discussionsupporting
confidence: 67%
“…24,25 Our finding of an increased risk of cervical cancer during pregnancy among smokers was expected, considering that smoking is a well-established risk factor for cervical cancer. 26 However, this has not previously been reported for PAC and was in contrast to the null finding for smoking and cervical cancer within 1 year post-delivery.…”
Section: Discussioncontrasting
confidence: 66%
“…There was a borderline association between immigrant background and lower risk of pregnancy‐associated cervical cancer both during and after pregnancy, which is likely due to a lower screening attendance among foreign‐born women 24,25 . Our finding of an increased risk of cervical cancer during pregnancy among smokers was expected, considering that smoking is a well‐established risk factor for cervical cancer 26 . However, this has not previously been reported for PAC and was in contrast to the null finding for smoking and cervical cancer within 1 year post‐delivery.…”
Section: Discussionmentioning
confidence: 54%
“…The risk increases to over 2 with a habit of approximately 20 cigarettes/day or 15 pack-years for invasive CC and about nine cigarettes/day or eight pack-years for preinvasive lesions. However, the risk subsides about 15 years after cessation of smoking ( 51 ). In terms of passive smoking as a risk factor for CC, the results are inconsistent.…”
Section: Resultsmentioning
confidence: 99%